Demo: Enhancing Smartphone Productivity and Reliability with an Integrated Display Cover - Hodges, Steve; Scott, James; Chen, Nicholas; Taylor, Stuart; Helmes, John; Wright, Phil; Walker, Laura; Trim, Nick; Grosse-Puppendahl, Tobias; Knierim, Pascal; Wood, Gavin; Denney, Thomas (UbiComp 2018: Extended Abstracts, 2018)
We describe a concept smartphone Display Cover, a secondary screen designed to improve productivity and convenience. Motivated by user research highlighting some of the limitations of current smartphones, the aim of this concept was to explore a practical solution which allows users to be more productive.